La norme et ses transgressions : polysémie de l’espace urbain (Fès / Tanger) dans le romanesque de Tahar Ben Jelloun (1973—2008) - Zdrada-Cok, Magdalena (Romanica Silesiana)
The article analyses the representations of Fez and Tanger in the fiction by Tahar Ben Jelloun. It proves that the contrast between these two cities, presented in his many works, illustrates antagonisms in the Moroccan society after 1956. The autobiographical thread of the way from Fez (the city of Norm) to Tanger (the city of Transgression), which emerges in such works as Harrouda (1973), L’Écrivain public (1983), Jour de silence à Tanger (1990), La Nuit de l’Erreur (1997), Sur ma Mère (2008), includes the issue of the writer’s political engagement and his objection to anachronistic social and moral norms. Tahar Ben Jelloun’s fiction, which is concentrated on the antinomy Fez — Tanger, becomes the area of difficult experience of freedom based on the symbolic breaking off with the father who symbolises restrictive tradition. Key words: The Moroccan society in 1950—1970, socio-political contestation, autobiographical literature, Fez, Tanger.